Motorcycle-Related Head and Limbs Injuries from Road Traffic Accident at a Second Level Hospital in Cameroon - Tinyami ErickTandi; KyungHee Kim; Tambetakaw Njang Gilbert; JaeWook Choi (Journal of Preventive Medicine And Care, 2019)
Motorcycles have been increasing used widely in various urban, suburban and villages in Cameroon with an increased in accidents resulting to injuries among the population. Head and limbs injuries are responsible for most of the cases encountered from related crashes. A prospective study on head and limbs injuries resulting from motorcycle crash were assessed among the different cases brought to the casualty and emergency department of the Kumba district hospital. Most of the injured cases were of motorcycle and other vehicle collisions 203 (47.65) and the least among motorcycle lone crash 51 (11.97). Motorcycle to motorcycle collisions accounted for 107 (25.12 %) of the cases. 65 (15.26%) were motorcycle with pedestrians related collision. Stepping up and facilitating the regulations on licenses and the use of personal protective equipment for riders, improvement of roads infrastructures with pedestrian path, expanding health facilities and equipment, and human resources for health as well as empowering the population on road safety measures will be very important for RTAs control measures of the nation.
Keywords: Head and limb injury